Seasonal influences on childhood lead exposure. - Yiin, L M (2000)
We conducted a study to examine seasonal changes in residential dust lead content and its relationship to blood lead in preschool children. We collected blood and dust samples (floors, windowsills, and carpets) to assess lead exposure. The geometric mean blood lead concentrations are 10.77 and 7.66 microg/dL for the defined hot and cold periods, respectively (p < 0.05). Lead loading (milligrams per square meter) is the measure derived from floor and windowsill wipe samples that is most correlated with blood lead concentration, whereas lead concentration (micrograms per gram) is the best variable derived from carpet vacuum samples. The variation of dust lead levels for these three dust variables (floor lead loading, windowsill lead loading, and carpet lead concentration) are consistent with the variation of blood lead levels, showing the highest levels in the hottest months of the year, June, July, and August. The regression analysis, including the three representative dust variables in the equations to predict blood lead concentration, suggests that the seasonality of blood lead levels in children is related to the seasonal distributions of dust lead in the home. In addition, the outdoor activity patterns indicate that children are likely to contact high leaded street dust or soil during longer outdoor play periods in summer. Consequently, our results show that children appear to receive the highest dust lead exposure indoors and outdoors during the summer, when they have the highest blood lead levels. We conclude that at least some of the seasonal variation in blood lead levels in children is probably due to increased exposure to lead in dust and soil.